Shrine politics and non-institutional religiosity : the Mrtvalj spring in the choreography of the pilgrimage shrine of St. John the Baptist at Podmilačje (Bosnia and Herzegovina) - Belaj, Marijana (Array, 2021)
The Mrtvalj spring is an integral part of a more complex sacred landscape, the center of which is the Shrine of St. John the Baptist located in Podmilačje near Jajce, Bosnia and Herzegovina. The shrine is a multi-confessional pilgrimage destination that is also very popular within the wider region. The Mrtvalj spring is one of the key stops in pilgrimage itineraries, but it is not only a sacred place within pilgrimage practices. In this paper the conceptualization of the Mrtvalj spring"s sacredness is examined as a reflection of the relationship between the religious and the political. The author analyzes the relationship between the shrine"s politics, which are based on the ideas of a "Bosnian Lourdes" and a shared shrine, and the spring as a focal point for the shared non-institutional practices of believers of various religious affiliations. She aims to show that a shared sacred site does not necessarily have to be controversial, and calls for a revalorization of non-institutional religiosity, which has proved to be a rich phenomenon for the study of interreligious relations.